Dampak Pandemi Covid-19 Terhadap Peningkatan Dispensasi Kawin - Nur Rofiq; Muhamad Ainun Najib; M Zidny Nafi’ Hasbi (Faculty of Law, Universitas Pattimura, 2022)
The impact of the COVID-19 pandemic in Indonesia has penetrated all aspects of people's lives, including the many cases of applying for a marriage dispensation. The purpose of this study was to find out the reasons for granting marriage dispensation to children under the age of 19 at the Magelang City Religious Court and how far the impact of the Covid-19 pandemic on the increase in marriage dispensations that occurred in Magelang City. The research method uses a normative juridical approach supported by field research. Then the object is examined using an analytical approach. The data collection techniques are interviews, observation, and documentation, as well as data analysis using qualitative descriptive. The results showed that the application for dispensation for marriage from before COVID-19 to the time of COVID-19 showed an extraordinary increase, reaching 300%. This can be seen from the data at the Magelang City Religious Court from 2017 to 2021. In 2017 the application and at the same time the marriage dispensation was granted by the Magelang City Religious Court as many as 7 cases, in 2018 there were 5 cases, in 2019 there were 6 cases, in 2018 there were 6 cases. 2020 from January to February there were 4 cases. Meanwhile, from March to December 2020, which was the beginning of the emergence of COVID-19, there were 22 cases and in 2021 there were 22 cases. However, the increase was not solely due to the opportunity behind the COVID-19 pandemic, but due to the enactment of the latest marriage law, namely Law Number 16 of 2019 which states that the minimum age for marriage is 19 years for both women and men. However, based on the old marriage law, namely Law No. 1 of 1974, there was no increase in the application for marriage dispensation but instead, it decreased.